1997
DOI: 10.1111/j.1600-0420.1997.tb00121.x
|View full text |Cite
|
Sign up to set email alerts
|

Perimetric probability maps to separate change caused by glaucoma from that caused by cataract

Abstract: We describe a new method for analysis of change in glaucomatous visual fields with the object to differentiate between changes caused by glaucoma from those caused by cataract. New pattern deviation change probability maps were developed from a prospectively collected glaucoma material and designed to be sensitive to changes in localized field loss, but to be unaffected by media-induced perimetric change. We compared the new change probability maps with the commercially available total deviation change probabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0
2

Year Published

1999
1999
2011
2011

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 88 publications
(42 citation statements)
references
References 16 publications
2
38
0
2
Order By: Relevance
“…AGIS applied pointwise linear regression analyses of threshold sensitivities, which are more sensitive to increasing media opacities than the EMGT progression criterion. 18 Filtering surgery often leads to progressive cataract, which in turn, leads to a slow and monotonic worsening of threshold values. Therefore, it is reasonable to assume that the authors' visual field analysis resulted in more false positive progression in filtered than in non-filtered eyes, thus leading to an apparent link between IOP change and progression.…”
Section: Discussionmentioning
confidence: 99%
“…AGIS applied pointwise linear regression analyses of threshold sensitivities, which are more sensitive to increasing media opacities than the EMGT progression criterion. 18 Filtering surgery often leads to progressive cataract, which in turn, leads to a slow and monotonic worsening of threshold values. Therefore, it is reasonable to assume that the authors' visual field analysis resulted in more false positive progression in filtered than in non-filtered eyes, thus leading to an apparent link between IOP change and progression.…”
Section: Discussionmentioning
confidence: 99%
“…Progression was defined as worsening of visual fields according to pre-defined criteria 6 based on computerized analyses using glaucoma change probability maps, 7 which have been shown to offer high sensitivity and specificity. 8,9 Glaucoma progression could also be identified as worsening of the disc, which was assessed by masked readings at a disc photography reading center.…”
Section: Methodsmentioning
confidence: 99%
“…Several studies have evaluated the performance of event analysis based on pattern deviation data compared to the use of total deviation data [5][6][7][8]. Pattern deviation analysis generally yields a smaller number of eyes with progression than total deviation analysis, as it does not account for diffuse loss from cataract progression [6,7] or for the diffuse glaucoma progression that differs from classical focal glaucomatous visual field deterioration [5]. In addition, in patients with moderate or advanced damage, pattern deviation calculations can also underestimate and bias the results [12,13].…”
Section: Discussionmentioning
confidence: 99%
“…By adjusting for diffuse changes in visual field sensitivity, pattern deviation analysis seeks to separate glaucomatous changes from those resulting from a cataract, on the assumption that a cataract causes a diffuse reduction in visual field sensitivity, whereas glaucoma leads to focal visual field changes [5]. A study in which the glaucomatous visual fields were tested for differences before and after cataract surgery showed that differences were much greater when using total rather than pattern deviation plots [6]. Therefore, pattern deviation analysis is thought to be less affected by cataract progression.…”
Section: Introductionmentioning
confidence: 99%